Genetic diversity of honeybees in different geographical regions of Siberia. Issue 5 (3rd September 2017) - Ostroverkhova, Nadezhda V.; Kucher, Aksana N.; Konusova, Olga L.; Kireeva, Tatjana N.; Sharakhov, Igor V.
Abstract: An assessment of the genetic diversity of nine microsatellite loci in honeybees of different origin (evolutionary lineages M, C, and hybrids) from different geographical regions of Siberia was conducted in order to find the genetic markers of the Siberian ecotype of dark-coloured forest bee ( Apis mellifera mellifera ). The greatest genetic diversity (both in the number of alleles and the calculated expected heterozygosity) was shown for loci A008, A113, Ap049, and A043 in honeybees from the Tomsk region, as bees from the southern districts had higher genetic diversity than bees from the northern districts. Honeybees from the Eastern region of Siberia (Yenisei population) had the lowest level of genetic diversity on these loci compared to Tomsk bee populations. Allele 162 pb of the locus A008, allele 126 bp of the locus A043, and allele 218 bp of the locus A113 can be considered as genetic markers of the A. m. mellifera Siberian ecotype .